Designing Educational Books for Children with Down Syndrome - Priambodo, Rio (Indonesian Journal of Visual Culture, Design, and Cinema, 2022)
Down syndrome is one of the common genetic disorders. It is experienced by children born with an abnormal number of chromosomes which causes mental retardation and characteristic physical characteristics. Currently in Indonesia, many schools have been established that are specifically provided for children with Down syndrome, one of which is SLB Puspa Melati. SLB Puspa Melati is located in the Tepus area, precisely in Pudak Hamlet, Gunungkidul Regency, D.I. Yogyakarta Province. The learning activities carried out at SLB Puspa Melati Tepus are continuously explored, this is as done in July 2017 where SLB Puspa Melati invited several graffiti actors (including writers) to draw with the students of SLB Puspa Melati, especially in drawing letters which were then assembled into the names of each student. This activity then inspired the author to design an educational book for down syndrome children, especially for students of SLB Puspa Melati. This design includes designing the fontstyle (variety of letters) that the author created, inspired by the author's fontstyle graffiti consisting of alphabets A to Z and numbers 0 to 9. The entire alphabet and numbers were designed using connecting lines as a tool for students to draw and identify letters and numbers after they were bolded.